G91(P) Salicylate levels in paediatric intentional overdose – are we over investigating?. (27th April 2015) - Daniel, J; Elliot, S
Abstract : Aim: To evaluate current practice in requesting salicylate levels in children presenting with intentional overdose. Background: Intentional overdose is a common presentation in children's emergency departments but the pattern of medications taken has changed over time. Over the last two decades use of aspirin (salicylate) has markedly reduced since recognition of Reye's Syndrome in children. Toxbase and NPIS advise salicylate levels are not required unless there is admission of ingestion, symptoms of salicylate toxicity or in the unconscious patient. It was noted that it remains common practice to check salicylate levels in children with intentional overdose. Methods: A retrospective review of all children presenting with intentional overdose at a busy two site acute trust. Case note and blood results review of all children coded as poisoning between July – December 2012, excluding children with accidental overdose. Results: There were 59 episodes of intentional overdose with 53 females and 6 males. The average age was 14yrs (11 – 16yrs). 73% (43) of the patients were asymptomatic. The most common drug taken was paracetamol (46%), followed by ibuprofen (20%) and cocodamol (11%). Only 2 patients (3%) admitted taking salicylate. The majority of initial blood tests were taken in the emergency department (71%). 83% (49) had salicylate levels measured and only 4% (2) had abnormal levels. Both of these patients had admitted salicylate ingestion. No patients who denied salicylate ingestion were found to have raised levels. Salicylate levels were deemed appropriate and useful in 4 (8%) patients due to history or symptoms. It was also observed that there was frequent requesting of a wide range of unnecessary blood tests including CK, FBC and CRP. Conclusion: There is considerable over testing of salicylate levels in children with intentional overdose. Our results found the test appropriate in only 4 (8%) patients. The laboratory test itself is relatively cheap however, in combination with other unnecessary tests, the cumulative cost is significant. We advise improved education as to the indications for salicylate levels as part of aiming to reduce unnecessary investigations and costs in children's emergency department.